2022
DOI: 10.1177/08839115221085736
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve regeneration by thiolated chitosan hydrogel containing Taurine: In vitro and in vivo study

Abstract: About 2.8% of trauma sick persons hurt from peripheral nerve damages, thus, numerous approaches are using to improve peripheral nerve regeneration. In the current study, the efficacy of several dosages of Taurine for peripheral nerve regeneration was evaluated. About 0.1%, 1%, and 10% (w/w) of Taurine were added into thiolated chitosan hydrogel and its features including morphology, swelling properties, weight loss, hemo-, and cytocompatibility were assessed. Hydrogels’ functionality was evaluated by injecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…), polysaccharides (hyaluronic acid, chitosan, etc. ), and polyesters (P3HB and PHBV) improve cell-scaffold interaction, facilitating tissue regeneration ( Arslantunali et al, 2014 ; Ehterami et al, 2022 ). Biodegradable polymeric nerve conduits based on copolymers like poly-L lactide, polyurethane, and polyglycolic acid show promise as ideal scaffolds due to their bio-absorbability and mechanical characteristics ( Cingolani et al, 2018 ; Ehterami et al, 2021 ).…”
Section: Nerve Repair With Tissue Engineering Scaffoldsmentioning
confidence: 99%
“…), polysaccharides (hyaluronic acid, chitosan, etc. ), and polyesters (P3HB and PHBV) improve cell-scaffold interaction, facilitating tissue regeneration ( Arslantunali et al, 2014 ; Ehterami et al, 2022 ). Biodegradable polymeric nerve conduits based on copolymers like poly-L lactide, polyurethane, and polyglycolic acid show promise as ideal scaffolds due to their bio-absorbability and mechanical characteristics ( Cingolani et al, 2018 ; Ehterami et al, 2021 ).…”
Section: Nerve Repair With Tissue Engineering Scaffoldsmentioning
confidence: 99%
“…It has been indicated that a scaffold pore size in the range of 100-400 μm is favorable for cell colonization, proliferation, and penetration [9]. Chitosan (CS) is well-known to be excellent in biocompatibility, biodegradability, antimicrobial property, wound healing, cell proliferation, and tissue regeneration, is a linear polysaccharide composed of glucosamine and N-acetyl glucosamine with β, 1-4 glycosidic linkages; the latter is a moiety of glycosaminoglycans [10]. It is known that during the biomineralization processes living organisms are able to crystallize and deposit a wide range of minerals.…”
Section: Introductionmentioning
confidence: 99%
“…12 Chitosan is a natural biodegradable polymer; it is mainly a linear polymer consisting of 2-amino-2-deoxy-d-glucopyranose structural units that linked to gather by 1,4-glycosidic bonds. 13 It is characterized by the abundance of amino and hydroxyl groups, allowing it to be used as a natural adsorbent for the removal of pollutants. 14 One of chitosan’s most important bioactivities is anti-microbial activity.…”
Section: Introductionmentioning
confidence: 99%